Metastatic basal cell carcinoma: case series and review of the literature. (24th February 2016) - Tang, Simon; Thompson, Stephen; Smee, Robert
Abstract: Metastatic basal cell carcinoma is exceedingly uncommon, with a poorly defined natural history, and its incidence, risk factors, patterns of spread, prognosis and potential treatment options are not well understood. This retrospective single institution case series aims to shed light on these issues. Aggressive local management in patients with locoregional disease may result in long‐term survivors.